Association between social support and medication literacy in older adults with hypertension - Shen, Zhiying; Ding, Siqing; Shi, Shuangjiao; Zhong, Zhuqing (Frontiers in Public Health, 2022)
Background Reduced physical function and reduced social networks place older adults with hypertension at high risk for medication-related harm. Medication literacy is one of the preventable factors that affect the success of drug therapy for hypertension. However, little is known about the level of medication literacy and its influencing factors in older adults with hypertension. Objective The purpose of this study was to investigate the levels of social support and medication literacy, and the association between them in older Chinese adult patients with hypertension. Methods A total of 362 older adult patients with hypertension were investigated using a demographic characteristics questionnaire, the Chinese Medication Literacy Scale for Hypertensive Patients (C-MLSHP) and the Social Support Rating Scale (SSRS). Pearson correlation analysis, canonical correlation analysis (CCA) and hierarchical linear regression were used to analyse the relationship between social support and medication literacy. Results Our results showed that the mean scores for the C-MLSHP and the SSRS for older adult patients with hypertension were 23.89 (SD = 4.66) and 39.22 (SD = 5.53), respectively. The results of the Pearson correlation analysis suggested that the score for social support was positively correlated with the score for medication literacy (r = 0.431, P < 0.01). The results of CCA demonstrate that older adult patients with hypertension who had more subjective (rs = 0.682) and objective support (rs = 0.817) performed better in knowledge (rs = 0.633), skills (rs = 0.631) and behavior literacy (rs = 0.715). Hierarchical linear regression indicated that two dimensions of subjective support (B = 0.252, P < 0.001) and objective support (B = 0.690, P < 0.001) in social support were found to be independent predictors of medication literacy (R2 = 0.335, F = 19.745, P < 0.001). Conclusion Social support is positively associated with medication literacy in older Chinese adult patients with hypertension. The study highlights the importance of social support in promoting medication literacy among older adult patients with hypertension.